ANALISIS KRITIK SASTRA DENGAN PENDEKATAN PRAGMATIK PADA KHUTBAH SYIQSYIQIYYAH KARYA SAYYIDINA ALI R.A. - Naja Alwi Mawardy; Ahmad Nurcholish (Universitas Muhammadiyah Gorontalo, 2021)
This writing aims to analyze and interpret literary criticism with a pragmatic approach to Sayyidina Ali's sermon known as the